OPERA BATAK SISINGAMANGARAJA XII: MENGGALI SENI DAN TEATER TRADISI - sulaiman sulaiman; Rosta Minawati; Enrico Alamo; Sherli Novalinda (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Batak Opera is a traditional performing art comes from Batak area and its surroundings. The existence of this art is increasingly lost due to the shift and the lack of activists who faithfully maintain this ancestral art. In fact, Batak Opera in the past represented triumphed arts among Batak people. Technological advances which later formed a new paradigm in society made this traditional of art increasingly abandoned and even forgotten by its supporters. The creation (revitalization) of Batak Opera was constructed by a heroiccaritoSisingamangaraja XII. This Batak Opera show is packed by combining several elements of the Batak tradition arts. Data is obtained by interview about Batak Opera, both to the descendants of Sisingamangaraja XII as well as Batak people. Sisingamangaraja XII represents a hero who succeeded in unifyingTapanuli and conquering the Dutch company. SisingamangajaBatak Opera is about heroism, compassion and sacrifice. It is a Dramatic story for the daughter of Lopian, his favorite child died on his huge penetrated by Dutch bullets. The heroic story of TanoBatak experienced rearrangement, both characterization and events using several structures of tradi-tional and modern Indonesian theater. SisingamangarajaBatak Opera becomes a field of revitalization of art. Batak operas are cultivated in order torevive the Batak Opera performances and raising the story of Sisimangaraja XII.